El rol de la física en la formación del ingeniero - Garza Rivera, Rogelio Guillermo (UANL. Facultad de Ingeniería Mecánica y Eléctrica, 2001)
The present document analyses the importance of physics in the engineers upbringing based on the three curricular perspectives: conceptual, methodological and axiological. Theres three dimensions delimit the knowledge, skills, procedures, values that students must develop and the attitudes to guarantee them an integral education as well as their successful participation in a global society.